Evaluating the restoration of Lake Manzala after dredging using water quality parameters and zooplankton changes - Seliem M. El Sayed; Mahmoud H. Hegab; Moustafa S. Abdelhameed; Mohamed E. Goher (Scientific Reports, 2025)
Abstract Lake Manzala is the largest northern lake in Egypt and receives significant quantities of wastewater. This study was conducted in 2015 and 2022 (before and after dredging) to assess changes in physicochemical parameters [transparency, salinity, dissolved oxygen (DO), chemical oxygen demand (COD), biological oxygen demand (BOD), and nutrients] as well as the community composition of zooplankton in relation to the dredging process. Water quality parameters, particularly salinity, classified the different lake sites into three groups (north, middle, and south) in 2015 and two groups (north-middle and south) in 2022. The highest values for transparency, salinity, and DO were recorded in the northern sector, while the highest values for BOD, COD, and nutrients were found in the southern sector. A total of 43 zooplankton species were identified in 2015, compared to 31 species in 2022. Notably, the number of saline species increased in 2022 to 12 species, and their distribution extended into the northern and middle sectors. Additionally, principal component analysis (PCA) revealed that zooplankton species could be divided into saline and freshwater groups. The study concluded that the chemical parameters and zooplankton composition in 2022 differed significantly from those in 2015 due to dredging, which altered the lake’s ecology by increasing salinity and reducing nutrient levels, particularly in the northern and middle regions.